LEGAL PROTECTION OF TAXPAYERS WHO ARE NOT INSURED CORPORATE INCOME TAX FOR THE BLOCKING OF ASSETS BY THE DIRECTORATE GENERAL OF TAXES - Humala Setia Leonardo Napitupulu; Ramlani Lina Sinaulan; Gatut Hendro Tri Widodo (Scholar Express Journals, 2023)
The research method used is a normative juridical legal approach . This research using a statutory research approach ( Statue Approach ) and a case approach ( Case Approach ) which are principally sourced from primary legal materials and secondary legal materials as well as tertiary legal materials with legal material analysis techniques using grammatical interpretation techniques, systematic interpretation, and teleological interpretation. The results of the study show that requests for blocking of taxpayer assets stored in Financial Services Institutions are carried out without proper procedures and are not in accordance with the criteria for taxpayers, because Irma Maria Polana is not a tax bearer for corporate taxpayer tax debts. Legal protection for taxpayers who are not corporate taxpayers, namely, tax bearers who are harmed by the actions of government officials can file a lawsuit with the district court and ask for compensation and rehabilitation of good name and compensation for the period of blocking they have served, while compensation is Rp. 100,000 (one hundred thousand rupiah) every day. As for the suggestion in this study is that government officials , in this case the Director General of Taxes, are more careful in determining the position of a person in terms of the tax bearer and in making a decision letter it should be done with a fixed procedure and pay attention to the general principles of good governance and not conflict with applicable laws and regulations so that the same dispute does not occur by other taxpayers or other tax bearers
Keywords: Taxpayer; Taxpayer Insurer; Corporate PPH